Path morphology of the Testis in White Outbreed Rats During Intoxication with Energy Drink (Eurasian Journal of Research, Development and Innovation, 2022)
In recent years, there has been a growing demand for energy drinks among young people. However, the effect of energy drinks on the reproductive system, including the testes, has not yet been fully studied. This article presents an analysis of pathomorphological changes in the testis tissue under the influence of energy drinks in 3-month-old white rats